Human skin temperature and mosquito (Diptera: Culicidae) blood feeding rate - Grossman, G L; Pappas, L G (Journal of medical entomology, 1991)
The relationship between skin temperature and mosquito blood feeding behavior was examined in nine human subjects. A system implementing computer control of skin temperature was utilized during blood feeding sessions in which feeding behavior (preforaging, foraging, probing, feeding) was timed and compared at five successive skin temperatures 29.0 degrees-36.2 degrees C). Preforaging, foraging, and probing times were not significantly different at the skin temperatures examined. Average blood meal size (3.3 microliters) also did not differ at these skin temperatures, but the time of engorgement decreased from 249.3 s at 30.8 degrees C to 100.7 s at 36.2 degrees C. The decreased feeding time resulted in an increase in feeding rate from 1.1 microliter/min (29.0 degrees C) to 2.2 microliters/min (36.2 degrees C).